Staphylococcus aureus persistence in osteocytes: weathering the storm of antibiotics and autophagy/xenophagy - Gunn, Nicholas J.; Kidd, Stephen P.; Solomon, Lucian B.; Yang, Dongqing; Roscioli, Eugene; Atkins, Gerald J. (Frontiers in Cellular and Infection Microbiology, 2024)
Staphylococcus aureus is a major causative pathogen of osteomyelitis. Intracellular infections of resident bone cells including osteocytes can persist despite gold-standard clinical intervention. The mechanisms by which intracellular S. aureus evades antibiotic therapy are unknown. In this study, we utilised an in vitro S. aureus infection model of human osteocytes to investigate whether antibioticmediated dysregulation of autophagy contributes to this phenomenon. Infected or non-infected osteocyte-like cells were exposed to combinations of rifampicin, vancomycin and modulators of autophagy. Intracellular bacterial growth characteristics were assessed using CFU analysis, viable bacterial DNA abundance and the rate of escape into antibiotic-free medium, together with measures of autophagic flux. Rifampicin, alone or in combination with vancomycin, caused a rapid decrease in the culturability of intracellular bacteria, concomitant with stable or increased absolute bacterial DNA levels. Both antibiotics significantly inhibited autophagic flux. However, modulation of autophagic flux did not affect viable bacterial DNA levels. In summary, autophagy was shown to be a factor in the hostpathogen relationship in this model, as its modulation affected the growth state of intracellular S. aureus with respect to both their culturability and propensity to escape the intracellular niche. While rifampicin and vancomycin treatments moderately suppressed autophagic flux acutely, this did not explain the paradoxical response of antibiotic treatment in decreasing S. aureus culturability while failing to clear bacterial DNA and hence intracellular bacterial load. Thus, off-target effects of rifampicin and vancomycin on autophagic flux in osteocyte-like cells could not explain the persistent S. aureus infection in these cells.